2020
DOI: 10.1016/j.omtm.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Fast SEC-Based Protocol to Isolate Human Plasma-Derived Extracellular Vesicles for Transcriptional Research

Abstract: Extracellular vesicles (EVs) are membranous structures that protect RNAs from damage when circulating in complex biological fluids, such as plasma. RNAs are extremely specific to health and disease, being powerful tools for diagnosis, treatment response monitoring, and development of new therapeutic strategies for several diseases. In this context, EVs are potential sources of disease biomarkers and promising delivery vehicles. However, standardized and reproducible EV isolation protocols easy to implement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 56 publications
8
19
0
Order By: Relevance
“…As per MISEV guidelines, we first measured the purity of isolated EV fractions. We showed an increase in the expression of proteins enriched in exosomes, TSG101 and CD81 in F7–10 as reported previously (32, 33). While F10 was not completely free of contamination by lipoproteins (ApoA1) and non-exosomal proteins (Cyt C), it also showed the presence of sEVs (~56.3 nm, data not shown).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As per MISEV guidelines, we first measured the purity of isolated EV fractions. We showed an increase in the expression of proteins enriched in exosomes, TSG101 and CD81 in F7–10 as reported previously (32, 33). While F10 was not completely free of contamination by lipoproteins (ApoA1) and non-exosomal proteins (Cyt C), it also showed the presence of sEVs (~56.3 nm, data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…To validate SEC-based EV isolation in our study, as per MISEV guidelines (29) we analyzed each fraction (F1–12) for protein yield and expression of exosome-specific (TSG101 and CD81) or non-exosomal markers or negative controls (Cyt C and Apo-A1). Protein concentration increased nearly exponentially starting in F7 through to F12 ( Figure 1B ) as shown before (32, 33). Exosomal markers TSG101 and CD81 were enriched in F7–10.…”
Section: Resultssupporting
confidence: 77%
“…Precleared ovarian follicular fluids might be kept at +4˚C for up to a week prior to EVs isolation [38]. The storage at +4˚C of purified EVs for up to 48 hours is allowed by protocol [39] (isolation by size-exclusion chromatography) and for 72 hours by protocol [40] (isolation by ultracentrifugation), while [41] recommend keeping isolated EVs on ice and process them as soon as possible. This ambiguity indicates the necessity of careful examination of the EVs instability phenomenon at +4˚C.…”
Section: Introductionmentioning
confidence: 99%
“…No direct experimental evidence for this route was reported for EVs in peer-reviewed papers, but multiple researchers warned that this process might occur during storage [6,20,33,42]. Some studies and protocols reported the usage of low protein binding tubes for EVs storage or handling [32,41,[43][44][45] with no experimental basis for this choice. Recently a patent for hydrophilic polymeric coating/additive to prevent EV adsorption was published [46] together with commercial EV-Save™ blocking reagent (058-09261, FUJIFILM Wako Pure Chemical Corporation).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of extracted protein was determined by BCA assay. 17 Proteins were separated using 12% SDS-polyacrylamide gel electrophoresis before transferred to polyvinylidene fluoride (PVDF) membranes using a wet membrane apparatus and blocked for 1 h with PBS containing 5% skimmed milk powder. 18 Details of primary antibodies used are in Table 3 .…”
Section: Methodsmentioning
confidence: 99%